Automotive brake systems - Halderman, James D. 1943- (Prentice Hall multimedia series in automotive technology, 2000)
For courses in Automotive Brake Systems or Chassis Systems in colleges or proprietary schools.Unlike other books--which seem to offer little more than service manual material--Automotive Brake Systems reflects Halderman's real world experience. It offers complete coverage of the parts, operation, design, and troubleshooting of brake systems, and answers the "why's" along with the "how's."